Optimasi Formula Gel Antioksidan Ekstrak Etanol Buah Bligo (Benincasa hispida) dengan Metode Simplex Lattice Design (SLD): Antioxidants Gel Formula Optimation of Bligo Fruit Ethanolic Extract (Benincasa hispida) by Simplex Lattice Design (SLD) method - Suryani Suryani; Andi Nafisah; Syahrir Mana'an (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Benincasa hispida has many benefits including as antioxidant. This study aims to evaluate the effect of Carbomer 940, HPMC and NaOH concentrations in antioxidant gel formula and to determine Carbomer 940, HPMC and NaOH concentrations that could produce the optimal antioxidant gel formula. Benincasa hispida was extracted by maceration method and antioxidant activity was tested by DPPH method. The antioxidant gels were formulated with variety combinations of Carbomer 940, HPMC and NaOH. The optimal gel formula was obtained by Design Expert 7.1.5 with Simplex Lattice Design method. The physical characteristic of optimal gel formula was retested and compared with the results of Simplex Lattice Design .The results showed that antioxidant activity of Benincasa hispida ethanolic extract has potent activity with the IC50 40,28 μg/mL. The increasing concentration of Carbomer 940, HPMC and NaOH possessed the high coefficients viscosity (cPs) with the value of 4366, 4133 and 3750 respectively. The increasing concentration of NaOH possessed pH and dispersive power of the gel with coefficients of 11,0 and 5,21 respectively. The desirability values suggested by Simplex Lattice Design were 1,000 with component variation of the optimal formula were Carbomer 940 1,5%, HPMC 0,5% and NaOH 0,4%. The significance test of the optimal formula compared to the results of laboratory experiments showed the significance of viscosity of 0,130, the dispersive power of 0,348 and pH of 0,184 that means there was no significant difference between the prediction values by using Simplex Lattice Design and results of laboratory experiments. It was indicated that significance values of each responses were over 0,05 (p>0.05).